DEVELOP A LOW-CALORIE PRODUCT BRAND IMAGE THROUGH PRODUCTION PROCESS INNOVATION FOR LEGIT CRACKERS MSMES - Yukianti, Chiara Rizka; Tunjungsari, Hetty Karunia (Graduate Program of Universitas Tarumanagara, 2024)
Legit Crackers is an MSME that produces snacks in the form of high quality and low-calorie mackerel fish crackers. The growth of MSMEs also drives Indonesia's economic growth so it can be said that MSMEs have a large contribution. Fish crackers are a popular snack among Indonesian people, with various types and interesting flavors. However, like many other MSME businesses, the fish cracker business also faces a number of problems that need to be overcome. One solution is to develop product formulas and brand images. This is important because good product quality can influence the awareness, trust and confidence of potential buyers. For Legit Crackers, a low-calorie snack business that was founded in 2017, building a brand image is a challenge. To increase marketing potential, good and unique product development, packaging and promotions are carried out. Development of a comprehensive strategic plan to overcome production efficiency problems, improve business image, and open access to international markets. In this context, the Universitas Tarumanagara PKM team is committed to assisting Legit Crackers in improving its business brand image. PKM activities aim to help Legit Crackers partners innovate and develop market potential for low-calorie snack products. It is hoped that this will improve consumer brand image towards Legit Crackers, develop the low-calorie snack market potential and penetrate the global market.